The meaning of the positions «left» and «right»: information, contrast and juvenile political participation - San Martín Ulloa, René (Última Década, 2020)
The present report summarizes part of the investigation carried out by the author along with three fellowmates, as part of his entitlement seminar. Such study compares the meaning ascribed by Non Politically Identified high school students to «left» and «right» and the meaning adscribed by those students who do have a polical identification: students from cities with more than 30.000 denizen of the Province of Valparaiso (N=22.111). The results commented in this article are referred to comparisons in terms of Semantics Richness and grades of Antagonism, Differentiation and Non Differentiation observed between «left» and «right» among the different groups, highlighting the implicancies for the juvenile political participation, the descovery of high signs of correlation between Antagonism and Semantics Richness and between the latter and Non Differentiation.